The Relationship Between Training, Talent, Technological Systems, and Personality on Employee Competency: Literature Review - Fitri, Dian; Ratnasari, Sri Langgeng; Suyanto, Suyanto; Sultan, Zulkifli (Devotion : Journal of Research and Community Service, 2024)
Employee competency is a crucial factor in organizational success. This paper explores the multifaceted relationship between four key elements that contribute to competency: training, talent, technological systems, and personality. We review existing literature on the impact of training programs on skill development and knowledge acquisition. We then examine the role of inherent talent and its influence on the learning process and ultimate competency. The paper further investigates how technological systems can both enhance and challenge employee competency, depending on their design and user characteristics. Finally, we analyze the influence of personality traits on an individual's approach to learning, technology adoption, and overall performance. Through this comprehensive review, we aim to shed light on the complex interplay between these factors and their combined effect on employee competency. This knowledge can be valuable for organizations in designing effective development programs that foster a competent and adaptable workforce.